Anthocyanin profile, antioxidant activity and total phenolic content of a strawberry (Fragaria × ananassa Duch) genetic resource collection. (August 2020) - Dzhanfezova, Tsaneta; Barba-Espín, Gregorio; Müller, Renate; Joernsgaard, Bjarne; Hegelund, Josefine Nymark; Madsen, Bjoern; Larsen, Dorthe H.; Martínez Vega, Mabel; Toldam-Andersen, Torben Bo
Abstract: Screening of strawberry anthocyanin composition and antioxidant capacities are important in the characterization and development of sources of natural colors. Here, Fragaria vesca (wild strawberry) and three commercial (cultivars 'Elsanta', 'Korona' and 'Honeyoe') and 14 non-commercial cultivars of Fragaria  ×  ananassa Duch. were characterized in terms of anthocyanin content and composition, total phenolic content and antioxidant activities for two consecutive growing seasons. Twelve non-commercial strawberry cultivars had higher anthocyanin contents when compared to previous reports, varying between 1.13 and 1.89 g kg -1 fresh weight (fw) in total, with pelargonidin 3-O-glucoside as the major (50–90%) and cyanidin 3-O-glucoside as the second most abundant (1–47%) anthocyanins. Among the characterized cultivars, S 94 combined high antioxidant activities (4.6 mmol Trolox equivalents g -1 fw and 24.6 mmol Fe 2+ g -1 fw on average for both years) and total anthocyanin (1.76 g kg -1 fw) and cyanidin 3-O-glucoside contents. Furthermore, the breeding potential of wild strawberry was highlighted as it had the highest antioxidant activity among tested cultivars and 44% of anthocyanins as cyanidin-3-O-glucoside. This study identified strawberry cultivars with traits desirable for colorants, which might guide future breeding programs for healthier strawberries.